Effect of antigen stimulation on the oxidative stress parameters in sperm of outbred and inbred rabbits. Issue 4 (4th July 2017) - Tanchev, Svetlin; Dimitrov, Stanimir; Nikolova, Galina; Karamalakova, Yanka; Ivanova, Donika; Hristova, Deyana; Georgieva, Svetlana; Zheleva, Antoaneta; Petrov, Vladimir; Gadjeva, Veselina
ABSTRACT: The presence of an increased oxidative stress during antigen stimulation was established in the sperm of inbred rabbits by evaluation of the level of real-time free radical formation (ROS and Asc ), final products of oxidation of lipids (MDA) and the activities of antioxidant defence enzymes superoxide dismutase (SOD) and catalase (CAT). There was not a significant difference between levels of ROS, Asc and MDA in inbred and outbred rabbits before immunization. The immune response, represented by levels of ROS and Asc of inbread and outbread rabbits were statistically significantly higher compared to those before immunization ( p = 0.0001 and p = 0.00001) Moreover, the levels of ROS in the sperm of inbread rabbits were statistically significantly higher compared to outbread rabbits ( p < 0.05). Oxidative stress was accompanied by an adaptive increase of SOD and CAT activities during the immune response, compared to those before immunization. Furthermore, the increased SOD and CAT activities appeared to be sufficient to inactivate the oxidative stress. We measured reduced levels of ROS, Asc and MDA 30 days after immunization. When immune response reduced, the observed SOD and CAT activities tended to return to the values before immunization. That might have been connected with the decreased oxidative burden. However, CAT activities remained about 1.5 times higher than that before immunization. In conclusion, our results indicate that the administered antigen stimulation induces oxidative stress in both groups inbred and outbred rabbits.